2023
DOI: 10.17159/sajs.2023/14905
|View full text |Cite
|
Sign up to set email alerts
|

Exploring perspectives of research ethics committee members on the governance of big data in sub-Saharan Africa

Abstract: Interest in the governance of big data is growing exponentially. However, finding the right balance between making large volumes of data accessible, and safeguarding privacy, preventing data misuse, determining authorship and protecting intellectual property remain challenging. In sub-Saharan Africa (SSA), research ethics committees (RECs) play an important role in reviewing data-intense research protocols. However, this regulatory role must be embedded in a context of robust governance. There is currently a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Rahimzadeh et al (2023) outlined how RECs in the United States are under-prepared to align with recent federal policy requiring that RECs review data sharing and management plans with attention to the unique ethical issues raised in AI research for health [13]. Similar research in South Africa identified variability in understanding of existing regulations and ethical issues associated with health-related big data sharing and management among research ethics committee members [14,15]. The effort to address harms accruing to groups or communities as opposed to individuals whose data are included in AI research has also been identified as a unique challenge for RECs [16,17].…”
Section: Recs and The Regulation Of Research Involving Aimentioning
confidence: 99%
“…Rahimzadeh et al (2023) outlined how RECs in the United States are under-prepared to align with recent federal policy requiring that RECs review data sharing and management plans with attention to the unique ethical issues raised in AI research for health [13]. Similar research in South Africa identified variability in understanding of existing regulations and ethical issues associated with health-related big data sharing and management among research ethics committee members [14,15]. The effort to address harms accruing to groups or communities as opposed to individuals whose data are included in AI research has also been identified as a unique challenge for RECs [16,17].…”
Section: Recs and The Regulation Of Research Involving Aimentioning
confidence: 99%
“…Their main purpose of protecting the dignity and rights of research participants is to foster social trust in research as well as assess its social value [ 9 ]. RECs play a pivotal role in the review and governance of all research including data-intensive research [ 10 , 11 ]. However, traditional ethics oversight mechanisms and practices may not be well placed to guarantee adequate oversight of data-intensive research given the unique and novel challenges presented by digital technologies and artificial intelligence (AI) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we conducted the first empirical survey in SSA in which awareness and perspectives of REC members were explored specifically relating to the review of data-intense research protocols and data governance in SSA [ 11 ]. At the time, it was unclear how REC members navigate governance structures and processes and review such protocols.…”
Section: Introductionmentioning
confidence: 99%